Motivacija učencev skozi čas - analize časovnih trendov v mednarodnih raziskavah znanja - Gril, Alenka (Šolsko polje, 2013)
Motivation is the key element in understanding student's success in school processes and learning. The changes over time in the effects of interest and perceived self-competences, as well as active classes, in the academic achievements of eighth-graders in Slovenia and three European countries have been studied. The analyses were based on the international achievement studies TIMSS and CIVED/ICCS. The time trends show that the achievements of eighth-graders has increased, as well as perceived selfcompetences on various domains - mathematics, science, civic education. The interest in various subject areas of eighth-graders in all four countries has decreased. The active classes of different subjects have increased in all countries. The most powerful predictors of achievement in all of the compared countries are SES and perceived self-competencies, and they are positively related and stable in all of the domains and countries. The effect of interest on the achievement has decreased in the last decade, and has been shown to have a negative effect in several countries, as well as the active classes. SES is stable and positively related to achievement in various domains in all countries, as well as the language at home. The effect of the student's genderis less stable, and decreases lately.
Keywords: knowledge; znanje; učna motivacija; matematika; achievement motivation; international achievement studies; naravoslovje; mathematics; državljanska vzgoje; osnovnošolci; science; civic education; časovni trendi; elementary school students; TIMSS; CIVED/ICCS; time trends; education; vzgoja in izobraževanje; mednarodne raziskave